ANALISIS PENGARUH TINGKAT SUKU BUNGA, NILAI TUKAR DAN INFLASI TERHADAP HARGA SAHAM PERBANKAN PADA TAHUN 2011-2020 - Muslimin, Huda Mulya; Boedirochminarni, Arfida; Susilowati, Dwi (Program Studi Ekonomi Pembangunan, 2021)
The purpose of this study is to reaffirm the effect of interest rates, exchange rates and inflation on banking stock prices in 2011-2020 and to strengthen the results of previous studies. The data sources for this research were obtained from the official website of Bank Indonesia, the Central Bureau of Statistics, and the Indonesia Stock Exchange. The population in this study were 45 banks. The research sample used was purposive sampling technique. The analysis technique used is a quantitative technique, then it is estimated by means of a qualitative test of the influence of the variables both simultaneously and partially and using a panel data regression model test, classical assumptions, linear data panel analysis to the coefficient of determination r-square. The results showed that the results of the separate test showed a positive and significant effect on the interest rate variable, then the exchange rate variable obtained a positive and significant effect while the inflation variable had a negative and insignificant effect. This is because if inflation occurs, the price will decrease so that inflation must continue to increase and in such a way that there are no fluctuations in order to stabilize inflation.